Leukocyte-borne α(1, 3)-fucose is a negative regulator of β2-integrin-dependent recruitment in lung inflammation. Issue 2 (26th August 2016) - Buffone, Alexander; Nasirikenari, Mehrab; Manhardt, Charles T; Lugade, Amit; Bogner, Paul N; Sackstein, Robert; Thanavala, Yasmin; Neelamegham, Sriram; Lau, Joseph T Y
Abstract: Leukocyte recruitment in inflammation is a multistep, sequential cascade where the initial step is the selectin-dependent tethering, followed by the formation of firmer integrin-mediated adhesive forces leading to extravasation. The α(1, 3)-fucose-containing sialyl-Lewis X (sLe X ) is the archetypical ligand on leukocyte surfaces mediating selectin interactions. Canonically, disruption of α(1, 3)-fucose formation ablates selectin-mediated adhesion, dramatically reducing trafficking. We report a paradoxical response to α(1, 3)-fucose deficiency in which the loss exacerbated rather than attenuated leukocyte recruitment in a murine model of acute airway inflammation. The architecture of the capillary-dominated vasculature in the lung minimized the importance of the selectin dependent step, and we observed that α(1, 3)-fucose deficiency augmented CXCR2-mediated Rap1-GTP signaling to enhance the β2 -integrin-ICAM-1-binding axis. The data disclose a previously unknown function for α(1, 3)-fucose, in which this structure negatively regulates the integrin activation step in leukocyte recruitment.